2012
DOI: 10.1111/j.1600-0714.2012.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor copy number in potentially malignant oral disorders and oral squamous cell carcinoma: a short communication and preliminary study

Abstract: The EGFR copy number may be a useful biomolecular marker to differentiate PMODs from OSCC. The EGFR was higher in non-homogeneous leukoplakias and in the advanced stages of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…1) It is present both in serum and saliva (soluble EGFR) . 2) Its tissue overexpression has been detected during the cancerogenesis of the oral mucosa . 3) It is frequently overexpressed in OSCC and in premalignant oral lesions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) It is present both in serum and saliva (soluble EGFR) . 2) Its tissue overexpression has been detected during the cancerogenesis of the oral mucosa . 3) It is frequently overexpressed in OSCC and in premalignant oral lesions .…”
Section: Introductionmentioning
confidence: 99%
“…2) Its tissue overexpression has been detected during the cancerogenesis of the oral mucosa . 3) It is frequently overexpressed in OSCC and in premalignant oral lesions . 4) Its tissue overexpression is significantly associated with poor prognosis in OSCC .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, EGFR can be considered as a marker of cell epithelial proliferation, of OED, and as the onset of progression from dysplasia to OSCC. 43 Bagan et al 26 reported that EGFR CNG is a potential marker for predicting malignant transformation of OED. The authors noted that EGFR CNG was significantly higher in malignant lesions and in non-homogeneous leukoplakia compared to homogeneous leukoplakia.…”
Section: Detection Methods Of Egfr In Oral Cancermentioning
confidence: 99%
“…3,17,31,35,49 In oral cancer specific tests to evaluate deletions, silent mutations or changes at amino acid level encoded in exons 18 to 21 have been used. 33 Bagan et al 26 studied the genomic amplification of EGFR in frozen tissue samples. Using Real-Time-PCR, they found a high rate of EGFR CNG in oral cancer when compared with potentially malignant lesions.…”
Section: Detection Methods Of Egfr In Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation